Lep-One Dessert as a Contemporary Food Innovation - Rhaina Rifka Nefindia; Lanang Maulana; Salma Tabina; Karyadi Hidayat (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This qualitative study analyzes the adaptive strategy of the innovative culinary product Lep One Desert, a modified version of the traditional Klepon cake. Facing the challenges of modernization, Lep One Desert maintains the visual identity of Klepon (green color and shredded coconut) while making a radical innovation by replacing the traditional palm sugar filling with a blend of caramel and chocolate. Using a descriptive case study approach, the research identifies conserved cultural values and examines how this flavor innovation serves as a key modernization strategy. Findings show that adopting global flavors (caramel and chocolate) successfully generates new appeal, aligning with contemporary trends. This tactic effectively preserves the core cultural identity while making the local culinary heritage competitive and relevant in the current market.